Regional Specificity of the Personality of the Bribe-Giver: the Experience of Sociological Analysis - R. R. Agishev; O. N. Barinova; I. V. Manaeva (Дискурс)
Introduction. A sociological analysis of the personality of the bribe-giver is given based on the study of data on the Republic of Mordovia. The relevance of the issue is determined by the following factors: the strengthening of the negative impact of corruption on all aspects of society and the state; the social mimicry of corruption, the stability of ideas in society about the ambivalence of corruption. The purpose of the article is to highlight the regional specifics of the identity of the bribe-giver.Methodology and sources. The neoclassical paradigm of the study of corruption links corruption phenomena with the decomposition of the state apparatus and the erosion of the moral foundations of society. In this vein, the authors explore the dual nature of corruption, that is, its conditionality by both the government and society. In the context of Durkheim's anomie theory, the motivational complex of bribe-takers is analyzed.Results and discussion. The objectives of the study required a mass survey (n = 400, ∆ ±5%), which represented the composition of the population of the region by gender, age, type of activity and type of locality. Within the framework of the study, a qualitative and quantitative description of the corrupt behavior of the bribe-giver was carried out, his motivational complex was revealed, and his subjective assessment of the dynamics of corruption and the effectiveness of anti-corruption policy was revealed. The following regional features of the personality of the bribe-giver are revealed: the age of the highest economic and social lability, the average level of corruption activity, the low size of the average amount of a bribe, acting as the initiator of a corrupt bribe, the perception of a bribe as a rational means of solving problems, pronounced negativism in assessing the authorities.Conclusion. Participation in corrupt transactions imposes a more or less pronounced imprint on the personality of the bribe-giver, which consists in the deformation of the practices of relations with representatives of state bodies, the gradual loss of immunity to criminal or semi-criminal activities, the partial degradation of socially significant moral values, the transformation of corrupt practices from a social anomie to a social norm.